The Effect of Electronic Storybook and Print Storybook on Students’ Reading Comprehension Skill Based on Their Learning Styles - Yayu Sri Rahayu; Januarius Mujiyanto; Suwandi Suwandi; Sri Wuli Fitriati (Universitas Negeri Semarang, 2022)
The change from printed to electronic content has an impact on students’ reading comprehension and reading style. This article presents experiments designed to assess the influence of electronic text on the reading comprehension of the second semester students of English Language Education Study Program. This study aims to ascertain whether there is a substantial difference in basic reading comprehension achievement between students with visual, auditory, and kinesthetic learning styles. In this article presents two experiments designed to assess the effect of electronic text on the basic reading comprehension of second-semester students. In the first trial, 72 students read either electronic or printed storybooks in learning basic reading comprehension course. This study found no statistically significant difference between open-ended questions and a test for measuring basic reading comprehension. There was, however, substantial statistical difference in reading comprehension between students with different learning styles, for the group who read the electronic versions of the stories, as determined by e-storybook. As measured by test of basic reading comprehension, their comprehension of the e-book stories was significantly greater. Thus the result of this research shows there are no there are no notable distinctions between the auditory, visual, and kinesthetic styles of learning derived from the basic reading comprehension learning outcomes of students who were taught using an electronic storybook or a print storybook.